Effective project management : guidance and checklists for engineering and construction - Ward, Garth G. F. (Hoboken, NJ : Wiley-Blackwell, John Wiley & Sons Ltd, 2018)
'This book provides the project manager with a quick reference and guide to tackling any situation or problem that they may be facing, without the need for extensive background research. It covers project initiation and execution, as well as the personal skills and techniques required to effectively manage projects'--
Execution 139 Section A Project Launch 140 Section B Establishing An Office 150 Section C Getting Organized 152 Section D Mobilization 159 Section E Client Relations 161 Section F Scope 163 Section G Estimates and Budget 166 Section H Accounting 170 Section J Planning and Scheduling 173 Section K Project Controls 176 Section L Variations/Changes/Claims 181 Section M Reporting 188 Section N ProjectMeetings 193 Section O Design 195 Section P Procurement 200 Section Q Installation and Construction 205 Section R Subcontracting 215 Section S Commissioning and Setting ToWork 219 Section T Contract Completion -- Close Out 222 Section U Post Project Activities 227 Part V Specialist Topics 233 Section A Completed and InspectedWork 234 Section B Coordination Procedure 238 Section C Cultural Issues 243 Section D.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 28, 2018).
Keywords: Project management; Leadership; Electronic books